Exploring the influence of culture on hearing help-seeking and hearing-aid uptake. (July 2015) - Zhao, Fei; Manchaiah, Vinaya; St. Claire, Lindsay; Danermark, Berth; Jones, Lesley; Brandreth, Marian; Krishna, Rajalakshmi; Goodwin, Robin
Abstract Objective: The purpose of this paper was to highlight the importance of cultural influence in understanding hearing-help seeking and hearing-aid uptake. Design: Information on audiological services in different countries and 'theories related to cross-culture' is presented, followed by a general discussion. Study sample: Twenty-seven relevant literature reviews on hearing impairment, cross-cultural studies, and the health psychology model and others as secondary resources. Results: Despite the adverse consequences of hearing impairment and the significant potential benefits of audiological rehabilitation, only a small number of those with hearing impairment seek professional help and take up appropriate rehabilitation. Therefore, hearing help-seeking and hearing-aid uptake has recently become the hot topic for clinicians and researchers. Previous research has identified many contributing factors for hearing help-seeking with self-reported hearing disability being one of the main factors. Although significant differences in help-seeking and hearing-aid adoption rates have been reported across countries in population studies, limited literature on the influence of cross-cultural factors in this area calls for an immediate need for research. Conclusions: This paper highlights the importance of psychological models and cross-cultural research in the area of hearing help-seeking and hearing-aid uptake, and consequently some directions for future research are proposed.